Five new Brazilian species of Fuminana Freytag (Hemiptera: Cicadellidae: Gyponini) with new records and key to males - Domahovski, Alexandre Cruz; Cavichioli, Rodney Ramiro (Zootaxa, 2022)
Five new Brazilian species of Fuminana Freytag, 1989 are described and illustrated: F. diaphana sp. nov. from states of Maranhão and Piauí, F. guaricica sp. nov. from Paraná State, F. incurvata sp. nov. and F. retorta sp. nov. from Rondônia State, and F. niluga sp. nov. from states of Acre, Pará, Rondônia and Mato Grosso. The female genitalia is described and illustrated for the first time and a revised genus description is presented. New distribution records are given and seven species are newly recorded from Brazil: F. astra (DeLong & Freytag, 1969), F. conspicua (DeLong & Freytag, 1969), Fuminana curra (DeLong & Freytag, 1969), F. extata Freytag, 1989, F. jaculum (DeLong & Freytag, 1969), F. signa (DeLong & Freytag, 1969) and F. superba (DeLong & Freytag, 1969). A key to males is provided as well as some taxonomic notes about the genus.